A Dynamic Framework for Mass-Energy Interaction: Exploring the Role of Time and Relativity (London Journal of Research In Science: Natural and Formal, 2025)
The relationship between mass and energy is well-established, yet the behavior of mass when  interacting with energy warrants further exploration. This study examines how the introduction of  time into the mass-energy interaction influences the behavior of mass. Furthermore, it investigates  whether the efficient utilization of energy could potentially enable travel at speeds exceeding that  of light. This paper extends the conceptualization of energy by considering mass not as a static  entity but as a dynamic quantity. It explores how mass distributes received energy and its behavior  under various values of energy and time. The investigation begins with the fundamental form of  mass, specifically the point energy mass, which is influenced by both energy and time. The study  then expands to encompass larger and more complex forms of mass, analyzing the generalized  effects of energy and time on their behavior. Additionally, the study examines the roles of space  and speed in relation to energy and time, incorporating in the investigation fundamental equations  of relativity. The findings suggest the possibility of mass traveling at speeds that would be  considered as limited until now, by setting appropriate mass factors.